Human gait modelling with step estimation and phase classification utilising a single thigh mounted IMU for vision impaired indoor navigation - Abhayasinghe, Kahala Nimsiri (Curtin University, 2016)
This research is focused on human gait modelling for infrastructure free inertial navigation for vision impaired. A pedometer based on a single thigh mounted gyroscope, an efficient algorithm to estimate thigh flexion and extension, gait models for level walking, a model to estimate step length and a technique to detect gait phases based on a single thigh mounted Inertial Measurement Unit (IMU) were developed and confirmed higher accuracies.